Zika virus infection in the Veterans Health Administration (VHA), 2015-2016 - Schirmer, Patricia L. (PLoS Negl Trop Dis, 2018)
BACKGROUND: Zika virus (ZIKV) is an important flavivirus infection. Although ZIKV infection is rarely fatal, risk for severe disease in adults is not well described. Our objective was to describe the spectrum of illness in U.S. Veterans with ZIKV infection. METHODOLOGY: Case series study including patients with laboratory-confirmed or presumed positive ZIKV infection in all Veterans Health Administration (VHA) medical centers. Adjusted odds ratios of clinical variables associated with hospitalization and neurologic complications was performed. PRINCIPAL FINDINGS: Of 1,538 patients tested between 12/2015-10/2016 and observed through 3/2017, 736 (48%) were RT-PCR or confirmed IgM positive; 655 (89%) were male, and 683 (93%) from VA Caribbean Healthcare System (VACHCS). Ninety-four (13%) were hospitalized, 91 (12%) in the VACHCS. Nineteen (3%) died after ZIKV infection. Hospitalization was associated with increased Charlson co-morbidity index (adjusted odds ratio [OR] 1.2; 95% confidence interval [CI], 1.1–1.3), underlying connective tissue disease (OR, 29.5; CI, 3.6–244.7), congestive heart failure (OR, 6; CI, 2–18.5), dementia (OR, 3.6; CI, 1.1–11.2), neurologic symptom presentation (OR, 3.9; CI, 1.7–9.2), leukocytosis (OR, 11.8; CI, 4.5–31), thrombocytopenia (OR, 7.8; CI, 3.3–18.6), acute kidney injury (OR, 28.9; CI, 5.8–145.1), or using glucocorticoids within 30 days of testing (OR, 13.3; CI 1.3–133). Patients presenting with rash were less likely to be hospitalized (OR, 0.29; CI, 0.13–0.66). Risk for neurologic complications increased with hospitalization (OR, 5.9; CI 2.9–12.2), cerebrovascular disease (OR 4.9; CI 1.7–14.4), and dementia (OR 2.8; CI 1.2–6.6). CONCLUSION: Older Veterans with multiple comorbidities or presenting with neurologic symptoms were at increased risk for hospitalization and neurological complications after ZIKV infection.